EKSPLORASI ETNOMATEMATIKA ISTANA MAIMUN DI SUMATERA UTARA - Nur Rahmi Rizqi; Jihan Hidayah Putri; Isra Suna Hasibuan (JURNAL EDUSCIENCE (JES), 2022)
Humans were not aware of various operations using basic mathematical concepts and ideas. For example, counting activities by referring to a number, weighing operations (duty, area, capacity and load), art, business activities (counting currencies, profit and loss, etc.) ) and building architecture (traditional housing). The aim of this study is to study and analyze the ethnographic findings from Maimun Palace, North Sumatra, to obtain background information on the development of ethnography for learning mathematics in the field of geometry. This type of research is exploratory research using an ethnographic approach. Based on the results of the research carried out, mathematical sections and blanks are used to carry out the manual operations of the Maimun Palace. No need to study theoretical math projects, they apply mathematical concepts in everyday life. There is evidence of ethnographic patterns expressed in various results of organized and advanced mathematical operations, including: 1) planning for the construction of Maimun Palace; and 2) the carving activity on the walls of Maimun Palace.